Estimation of Credibility of the Results of Measuring Temperature within Specimens of Wood Columns Obtained During Fire Tests - Feshchuk, Yurii; Pozdieiev, Serhii; Zmaga, Yana; Novhorodchenko, Alina (International Journal of Engineering and Technology, 2018)
Analysis of the results of experimental studies of wood columns mode of behaviour both having fire retardant coating based on OSB slabs and without any coating under standard time â€“ temperature curve fire conditions was realized. An assumption was made that thermocouple wires could be positioned along isotherm at a distance of at least50 mmfrom measuring thermojunctions (otherwise disturbance of the structure of isotherm itself possible). Due to specific features of thermocouples positioning within the specimen, this assumption calls in question of credibility of the obtained results of temperature indices measuring. Bearing this in mind we prepared calculation scheme of the specimen of wood column under study. We have composed finite elements scheme of specimen under study for heat engineering calculations. We simulated temperature distributions within the wood column specimen section at various moments of time and substantiated the obtained results. It was revealed in the course of the study conducted that the obtained results were adequate for relative error was as small as ca. 4.5% and Fisher test did not exceed appropriate tabulated value. Thus, assumption made does not affect in general credibility of the results of measuring thermal values within the layers of specimens obtained during fire tests.Â